Educational Media and Maternal Behavioral Change in Fetal Brain Health Stimulation - Wiwin Winarsih; Ika Fitria Elmeida (Poltekkes Kemenkes Tanjung Karang, 2026)
Health behaviors of pregnant women, such as stimulating fetal brain development, are efforts to improve long-term child development. This study aims to analyze the effectiveness of Education and Communication educational media (educational videos and leaflets) on the knowledge, attitudes, and behavior of pregnant women in conducting stimulation to improve fetal brain health. This study is a quasi-experimental pretest–posttest design conducted at the Kalianda Community Health Center, South Lampung Regency, from October to December 2025. The study included 30 pregnant women in the second and third trimesters, selected purposively and divided into two groups: the educational video intervention group (n = 15) and the brochure intervention group (n = 15). Data were collected using a validated and reliable questionnaire. Data analysis used descriptive statistics, the Shapiro-Wilk normality test, and the paired t-test. The results showed a significant increase in knowledge, attitudes, and behavior of pregnant women in both groups after the intervention (p < 0.05). The educational video group showed a greater increase in all variables than the leaflet group, with p-values of 0.000 for knowledge, 0.001 for attitude, and 0.000 for behavior. Conclusion: Educational videos are more effective than leaflets in improving pregnant women's knowledge, attitudes, and behavior regarding fetal brain stimulation.